Relationship between TCM syndrome classification and Type 2 diabetes - Too, Si Ying (Nanyang Technological University, 2021)
Type 2 Diabetes mellitus (T2DM) is a growing healthcare concern worldwide, with obesity and ageing identified as common risk factors. Till date, Traditional Chinese Medicine (TCM) has demonstrated effectiveness in lowering glucose levels when used in conjunction with conventional Western medicine (CWM). Objective: This paper aims to identify the relationship between TCM syndromes and T2DM for better glycaemic control. Method: A questionnaire-based survey was conducted on 260 patients at Singapore Thong Chai Medical Institution (STCMI). Results: Dual Deficiency in Qi and Yin (DDQY) was identified as the most common syndrome. It was observed that a longer duration of T2DM was associated with greater progression towards Dual Deficiency in Yin and Yang (DDYY). The mean age of patients with DDYY was the highest (73.1 ± 6.0 years), while patients with Excess Heat in the Stomach and Intestine (EHSI) syndrome had the lowest mean age (60.8 ± 9.5 years). There was significance between Haemoglobin A1c (HbA1c) levels and syndromes, with EHSI exhibiting the highest HbA1c level (7.8%). Conclusion: This study has provided an insight into the relationship between TCM syndrome classification and T2DM. However, further studies are required for a more comprehensive understanding of the distribution of syndromes in Singapore’s T2DM population.